“A JOURNEY TO ARMENIA, TURKEY AND CILICIA” BY THE BISHOP VARDAN ODZNETSI AS AN IMPORTANT SOURCE ON THE HISTORY OF THE CAUCASUS OF THE XVIII–XIX CENTURIES - Hapizov, Sahban Magomedovic; Akopan, Ajk Erdzanikovic (History, Archeology and Ethnography of the Caucasus, 2020)
The paper analyses the content of some of the parts of the work of the Armenian author of the 19th century bishop Vardan Odznetsi, kept in Matenadaran – the Institute of Ancient Manuscripts of Armenia. The full text of the work has not yet been published. The text is unique, as it is one of the last sources, written in the style of the Armenian historical literature of the Middle Ages. In his work, Vardan Odznetsi tells in detail about the court of the Georgian king Heraclius II (1720–1798). It also provides information about the Talysh Khan Mustafa and the Avar Nutsal Ummah Khan, known in historiography under the distorted name of Omar Khan. Thus, the chronicle of Odznetsi covers the history of not only Transcaucasia, but also the North Caucasus. In addition, the author describes in sufficient detail the events of the Crimean War (1853–1856).The information, provided by Vardan Odznetsi, is quite important in the context of studies devoted to the anti-Ottoman and anti-Iranian wars of the peoples of the Caucasus. In his work, a special attention is drawn to the scrupulous description of the invasion of Tbilisi in the summer of 1795 by the Iranian shah Aga-Muhammad Khan Kajar. With deep regret he tells about the destruction of the city, believing that this is the fault of the Georgian king, who showed political shortsightedness. In the 1790s Avar nutsal Ummah Khan (1761-1801) started to play an important role in the military-political events taking place in the South Caucasus, which is also mentioned in the work under review. He describes the relations of Umma Khan and his son-in-law Ibrahim-khan of Karabakh, their joint military campaigns on adjacent lands. At the same time, the work under study is an important source describing the transition of the kingdom of Kartli-Kakheti, and subsequently the entire Caucasus, under the protection of the Russian Empire. A study of this manuscript will serve as a more detailed source-study of the history of the Caucasus of the 18th – 19th centuries.
Keywords: Armenia; Dagestan; Georgia; Heraclius II; Ummah Khan; Aga Muhammad Khan